Findings that Red Meat Consumers are at Rise to Liver Cirrosis - Atif Shahzad, Muhammad Muzzamal Irshad, Areeba Rashad (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To study the link between cirrhosis and red meat intake and death in patients. Study Design: Prospective Study Place and Duration: THQ Hospital Kamalia.March 2019- Feb 2020 Methodology: This research involved a total of 200 individuals of both sexes with chronic liver disease. Two groups of patients were established. One group had a daily red meat intake more than 60 grammes, whereas the other consumes less than that limit. Both groups were compared in terms of mortality rates. SPSS 24.0 was used to examine the whole set of information. Results: Among 200 cases, frequency of males was significantly higher than that of females. Group I had mean age 50.2±6.45 years and in group II mean age was 52.13±17.97 years. We found that cirrhotic patients who consumed more than 60 grammes of red meat per day had a higher death rate (13 % vs. 5%) than those who consumed less than 60 grammes of red meat per day, with a p-value of 0.0004. Conclusion: Results from this study show that people with cirrhosis are more likely to suffer from unfavourable outcomes if they consume a diet high in red meat.